问题
解答题
已知数列{an}的前n项和为Sn=3n,数列{bn}满足b1=-1,bn-1=bn+(2n-1)( n∈N*). (Ⅰ)求数列{an}的通项公式an; (Ⅱ)求数列{bn}的通项公式bn; (Ⅲ)若cn=
|
答案
(Ⅰ)∵Sn=3n,
∴Sn-1=3n-1(n≥2).
∴an=Sn-sn=3n-3n-1=2•3n-1(n≥2).
当n=1时,2•30=2≠S1=3,
∴an=
2 (4分)3,n=1 2•3n-1,n≥
(Ⅱ)∵bn+1=bn+(2n-1)
∴b2-b1=1,
b3-b2=3,
b4-b3=5,
…
bn-bn-1=2n-3,
以上各式相加得
bn-b1=1+3+5+…+(2n-3)=
=(n-1)2(n-1)(2n-2) 2
∵b1=-1,∴bn=n2-2n. (9分)
(Ⅲ)由题意得Cn=
3n-1,(n≥2)-3,n=1 2(n-2)•
当n≥2时,
Tn=-3+2•0×3+2•1×32+…+2(n-2)×3n-13Tn=-9+2•0×32+2•1×33+2•2×34+…+2(n-2)×3n
相减得:-2Tn=(n-2)×3n-(3+32+33+…+3n-1)
Tn=(n-2)×3n-(3+32+33+…+3n-1)=(2n-5)•3n+3 2
Tn=
=-3,n=1
,n≥2(2n-5)•3n+3 2 (2n-5)•3n+3 2